Work Life Balance Model, Work Stress and Performance of Millennial Generation Online Taxibike Drivers - Ghani, Muhammad Alfa; Muttaqiyathun, Ani (Ridwan Institute, 2023)
The characteristics of the millennial generation are different from those of the previous generation. It is important to research the performance of those who currently dominate the world of work, especially the unprecedented work of online motorcycle taxi drivers. The purpose of this study is to determine the balance and work stress on the performance of millennial generation online motorcycle taxi drivers. This study used a quantitative approach, with the subject of online motorcycle taxi drivers, where the population is difficult to know. The sample was determined using the Lameshow formula so that a sample of 100 respondents was obtained. Teknik purposive sampling is used with the criteria of married drivers and classified as millennial generation. Data collection using questionnaires in the form of google forms is distributed directly to online motorcycle taxi drivers. Data analysis techniques use multiple linear regression analysis. The results showed that there was an effect of work life balance on performance, but on the contrary, there was no effect of work stress on performance.